Improved Flexural Strength, Modulus, KIC, and Compressive Strength of Epoxy Foam Modified with Natural Rubber (Journal of Technology Research, 2025)
The study developed new epoxy composites enhanced with natural rubber (NR) and sodium bicarbonate (SB) as a foaming agent. Adding NR improved the epoxy’s toughness, flexural strength, modulus, and fracture toughness (KIC), with optimal results at 10 vol% NR for flexural properties and 15 vol% NR for compressive strength. Increasing NR content led to greater expansion but reduced crosslinking and mechanical strength due to increased porosity. The improvement was attributed to small, uniformly dispersed NR phases that acted as energy dissipation centers, enhancing elasticity and load-bearing capacity. SEM analysis confirmed uniform dispersion of NR particles within the epoxy matrix, which significantly influenced mechanical performance.
Keywords: epoxy foam, natural rubber, depolymerized natural rubber, foaming agent, mechanical properties.